Synthesis and biological properties of new 1 beta-methylcarbapenems containing heteroaromatic thioether moiety - Shin, KJ; Koo, KD; Yoo, KH; Kang, YK; Park, SW; Kim, DJ (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
The synthesis and biological activities of a series of new 1 beta -methylcarbapenems 1a-h having heteroaromatic thioether moiety at C-5 position of pyrrolidine were described. Among these compounds, 1,2,3-thiadiazole derivative 1h showed the most potent antibacterial activity and advanced pharmacokinetics in comparison with meropenem. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: ANTIBACTERIAL ACTIVITY